Metabolite and transcriptome analyses reveal the effects of salinity stress on the biosynthesis of proanthocyanidins and anthocyanins in grape suspension cells - Zhao, Kainan; Lan, Yibin; Shi, Ying; Duan, Changqing; Yu, Keji (Frontiers in Plant Science, 2024)
Proanthocyanidins (PAs) and anthocyanins are flavonoids that contribute to the quality and health benefits of grapes and wine. Salinity affects their biosynthesis, but the underlying mechanism is still unclear. We studied the effects of NaCl stress on PA and anthocyanin biosynthesis in grape suspension cells derived from berry skins of Vitis vinifera L. Cabernet Sauvignon using metabolite profiling and transcriptome analysis. We treated the cells with low (75 mM NaCl) and high (150 mM NaCl) salinity for 4 and 7 days. High salinity inhibited cell growth and enhanced PA and anthocyanin accumulation more than low salinity. The salinity-induced PAs and anthocyanins lacked C5'-hydroxylation modification, suggesting the biological significance of delphinidin-and epigallocatechin-derivatives in coping with stress.The genes up-regulated by salinity stress indicated that the anthocyanin pathway was more sensitive to salt concentration than the PA pathway, and WGCNA analysis revealed the coordination between flavonoid biosynthesis and cell wall metabolism under salinity stress. We identified transcription factors potentially involved in regulating NaCl dose-and time-dependent PA and anthocyanin accumulation, showing the dynamic remodeling of flavonoid regulation network under different 2 salinity levels and durations. Our study provides new insights into regulator candidates for tailoring flavonoid composition and molecular indicators of salt stress in grape cells.